Veto Power Institutional Design in the European Union - Slapin, Jonathan B. (University of Michigan Press, 2011)
Jonathan B. Slapin traces the historical development of the veto privilege in the EU and how a veto- or veto threat- has been employed in treaty negotiations of the past two decades. As he explains, the importance of veto power in treaty negotiations is one of the features that distinguishes the EU from other international organizations in which exit and expulsion threats play a greater role. At the same time, the prominence of veto power means that bargaining in the EU looks more like bargaining in a federal system. Slapin's findings have significant ramifications for the study of international negotiations, the design of international organizations, and European integration.